Exploring the relationship between governance , Power of control and organizational conflict: a survey on small and medium italian family firms - Pezzillo Iacono, Mario; Martinez, Marcello; Mercurio, Lorenzo; Mangia, Gianluigi (Piccola Impresa / Small Business, 2013)
The aim of the paper is to develop and test a theoretical model concerning the relations among some variables of organisational design and the type and nature of the conflict in family firms. The theoretical model is developed through a variety of hypotheses which were tested by means of a survey on 175 firms registered at Italian Association of Family Businesses. In particular, conflict is analysed as a dependent variable with respect of: power concentration (measured in terms of founder centrality), formal governance mechanisms and generational involvement. The study examines how these three organizational features ultimately affect the functioning of a family firm, in terms of expected effect on task, process and relationship conflict. The results of empirical analysis confirmed that the level of power concentration directly influences task, process and relationship conflict, and that greater generational involvement fosters the development of relationship conflict.